2015
DOI: 10.3324/haematol.2015.127993
|View full text |Cite
|
Sign up to set email alerts
|

Use of killer cell immunoglobulin-like receptor genes as early markers of hematopoietic chimerism after double-umbilical cord blood transplantation

Abstract: Use of killer cell immunoglobulin-like receptor genes as early markers of hematopoietic chimerism after double-umbilical cord blood transplantationIt has been established that hematopoietic chimerism after double umbilical cord blood transplantation (dUCBT) can predict disease relapse and detect potential engraftment failure.1-3 The use of a precise method to evaluate residual host hematopoiesis is imperative because it has been reported that the risk of relapse is higher in patients with mixed chimerism. 4 Up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…In the context of HSCT, inclusion of KIR allele typing in addition to HLA typing may provide a better evaluation of HSC donor’s KIR + NK cell repertoire ( 21 , 59 , 60 , 66 , 67 ). An identification of those with the best antileukemic potential will provide a potential tool to determine an early posttransplant hematopoietic chimerism when donor and recipient have identical KIR genotypes ( 68 ) as well as the impact of KIR + NK cell alloreactivity on HSCT outcome ( 69 73 ). The functional relevance of typing both KIR and HLA genes at high resolution may help determine their combined effects on outcome of HSCT.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of HSCT, inclusion of KIR allele typing in addition to HLA typing may provide a better evaluation of HSC donor’s KIR + NK cell repertoire ( 21 , 59 , 60 , 66 , 67 ). An identification of those with the best antileukemic potential will provide a potential tool to determine an early posttransplant hematopoietic chimerism when donor and recipient have identical KIR genotypes ( 68 ) as well as the impact of KIR + NK cell alloreactivity on HSCT outcome ( 69 73 ). The functional relevance of typing both KIR and HLA genes at high resolution may help determine their combined effects on outcome of HSCT.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a retrospective study performed on a large cohort of AML patients reported that there was no impact of KIR3DL1/2DS1 or a haplotype-motif-based donor selection algorithm on OS and relapse after unrelated HLA matched HSCTs [151]. In line with HSCT protocols, the impact of KIR-L mismatches was investigated in adult patients after dUCBTs [152][153][154][155][156][157][158]. Once again, conflicting data were reported, which were linked either to the competing KIR models used or the heterogeneity of the patients and treatment modalities.…”
Section: Kir Models Used To Evaluate Nk Cell Alloreactivity and Clinical Outcomes After Allogeneic Hsctmentioning
confidence: 99%
“…When fully HLA-matched related or unrelated donors are unavailable, double umbilical CB transplantation (dUCBT) is an efficient alternative [12,13]. We have recently highlighted the importance of KIR genes in assessing early chimerism status after dUCBT [14]. It has been shown that CB NK cells mature rapidly after UCBT and harbor strong cytotoxic activity against blast cells [15].…”
Section: Introductionmentioning
confidence: 99%